PEMATAHAN DORMANSI BENIH KELAPA SAWIT (Elaeis guinensis Jacq.) MENGGUNAKAN KALIUM NITRAT (KNO3) DAN AIR KELAPA - Sinaga, Kaliamsyah; Hastin Ernawati Nur CC, Chotimah; Jagau, Yusurum (AgriPeat, 2021)
The aim of this study were, 1) to find out and study the effect of KNO3 immersion treatment on oil palm seed germination; 2) to find out and study the effect of coconut water immersion treatment on oil palm seed germination; 3) to find out and study the interactions that occur between KNO3 immersion treatment and coconut water to oil palm seed germination. This research was conducted in July 2019 until August 2019 in the Laboratory of the Department of Agriculture Cultivation, Faculty of Agriculture, Palangka Raya University using a Completely Randomized Design with 2 factors. The first factor is the concentration of KNO3: K0 (0%); K1 (0.2%); K2 (0.4%); K3 (0.6%) and the second factor is coconut water concentration, B0 (0%); B1 (60%); B2 (80%); B3 (100%). The parameters observed were first count germination, maximum growth potential, germination power, growth speed, radicle length, plumular length and dormancy intensity. The results showed that the treatment of KNO3 concentration significantly affected first count germination, maximum growth potential, germination rate, growth speed and dormancy intensity. Treatment of coconut water concentration significantly affected first count germination, maximum growth potential, germination rate, growth speed and dormancy intensity. The interaction between the treatment of KNO3 concentration and coconut water concentration had no significant effect on all observed parameters